GENESIS OF GREAT SAPHENOUS VEIN OBLITERATION AND ITS CLINICAL MANIFESTATIONS AFTER ENDOVENOUS LASER COAGULATION COMBINED WITH CROSSECTOMY DURING THE VARICOSE VEIN TREATMENT - M. Sh. Vakhitov; Z. M. Ulimbasheva; A. N. Ryzhov; M. A. Bykov; O. V. Danilchenko; A. Yu. Tsibin; D. Yu. Semenov (Вестник хирургии имени И.И. Грекова)
An analysis of results of the endovenous laser coagulation combined with crossectomy was made in 170 patients with varicose veins of lower extremities (CVI, CII–CV). Clinical and ultrasonic data were investigated during a period of 3–5 days (45 lower extremities) and followed up in 1–3 years after operation (194 lower extremities). Three years later the absence of reflux was observed in 95.9% of cases. In 51.1% of cases, 1–2 zones of parietal and segmental hemodynamical insignificant bloodstream were detected. A recanalization of the great saphenous vein along the whole length was revealed in 8 cases out of 194 (4.1%) patients. The bloodstream was provided by affluxes in the area of a shin and a wellhead afflux of the stump of the great suphenous vein. The ultrasonic picture of recanalization was similar to that observed in post-thrombophlebitic occlusion.